Analytical Study using Association Rules and Mean of Confidence to Analyze The Poverty Factors in Baghdad Capital of Iraq - Ali Sami; Ali Mohammed Sahan; Ghazi Johnny (Journal of Madenat Alelem University College, 2017)
Poverty is a negative phenomenon that seriously threatened the progress and growth of communities. Studying poverty using scientific research leads to identify the most important influential factors of this phenomenon. In this paper, the poverty in Iraq has been studied through a sample of families in Baghdad city which is the largest and most important city in Iraq. The relational databases as well as the factors related with poverty phenomenon including gender age, the number of family members, educational level, skilled, corruption, disability and disease, wars and disasters have been considered. The association rules and mean of confidence have been used to analyze the main factors for the spread of poverty phenomenon in order to provide clear diagnosis of the most influential factors in the proliferation of this phenomenon, which leads improve appropriate solutions to reduce the impact of these factors.